Anthropometric, physiological and selection characteristics in high performance UK junior Rugby League players - Till, K.; Cobley, S.; O`Hara, J.; Chapman, C.; Cooke, C. (Talent Development & Excellence, 2010)
The present study examined relationships between anthropometric, physiological and selection characteristics of junior (N=683; aged 13-16) representative Rugby League players who underwent a battery of tests (e.g., height; O2max) as part of a national talent development program. Considerate of playing position (categorised as `Outside-Backs`, `Pivots`, `Props`, `Backrow`), `Props` were more likely to be the relatively oldest and most mature. However, MANCOVA - with chronological age and maturation controlled - also identified that `Props` were the worst performing on physiological tests. To add, physiological characteristics did not differ according to relative age. Findings suggest that relationships between anthropometric and physiological characteristics are not consistent with biases in selection, which raises issues regarding identification for immediate and long-term player selection and development.